On the Solid Lubricity of Electrophoretically Deposited Carbon Nanohorn Coatings - Timothy MacLucas; Sebastian Suarez (Lubricants, 2019)
In this study, dahlia-type carbon nanohorns (CNH) have been deposited onto a stainless steel substrate by using electrophoretic deposition. Secondly, the lubrication properties of the carbon nanohorn coating have been researched by tribometry and compared to an uncoated reference. Wear track analysis has been conducted to identify the underlying tribo-mechanisms. Additionally, Raman spectroscopy was employed to study the structural changes of the CNH during dispersion and tribological testing. Furthermore, energy dispersive X-ray spectroscopy (EDX) was used in order to investigate the chemical composition of the wear tracks’ surface. This work has shown that CNH coatings have the ability to maintain effective solid lubrication on a polished stainless steel surface. A temporary friction reduction of 83% was achieved compared to the uncoated reference. Moreover, the lubricity was active for significant periods of time due to the formation of a Mg(OH)2 layer which provides a certain degree of substrate adhesion as it holds the CNH in the wear track. Once this holding layer wanes, the CNH are gradually removed from wear track resulting in an increase of the coefficient of friction. The complete removal of CNH from the wear track as well as considerable oxide formation was confirmed by EDX. Moreover, the amount of defects in the CNHs’ structure increases by being exposed to tribological strain. Adhesion has been identified as the dominant wear mechanism.